Complete mitochondrial genome of Sebastes owstoni (Scorpaenidae, Scorpaeniformes) from the East Sea, Korea. (1st November 2016) - Oh, Jina; Kim, Sung; Lee, Eun Kyung; Park, Jeong-Ho; Kim, Ki-Yong; Jang, Yo-Soon
Abstract: Sebastes owstoni is a popular fishery species in the north-western Pacific Ocean. To obtain basic information on its mitochondrial DNA (mtDNA), the complete mitogenome of S. owstoni was subjected to the next-generation sequencing. The assembled mtDNA was 16, 465 bp in length, comprising 13 protein-coding genes (PCGs), 2 rRNAs, 22 tRNAs and a control region. The complete mitogenome comprised of 27.7% A, 26.6% T, 17.3% G and 28.4% C, indicating a slight AT bias (54.3%). The start codon of all PCGs was ATG, with the exception of COX1 (GTG). The stop codons in the PCGs were mainly TAA, with the exception of ND1 and ND3 (TAG), ND4 (AGA) and Cytb (incomplete termination codon, T). All tRNAs had a typical cloverleaf shape, with the exception of tRNA Ser (AGY), which lacked the DHU arm. The sequenced mitogenome of S. owstoni can be used in genetics-based management initiatives or for constructing the mitochondrial lineages within Scorpaenidae.